Risk of recurrent severe hypoglycemia remains associated with a past history of severe hypoglycemia up to 4 years: Results from a large prospective contemporary pediatric cohort of the DPV initiative. Issue 3 (8th December 2017) - Pacaud, D; Hermann, JM; Karges, B; Rosenbauer, J; Danne, T; Dürr, R; Herbst, A; Lindauer, S; Müther, S; Pötzsch, S; Raile, K; Witsch, M; et al.
Abstract : Objectives: In a contemporary cohort of youth with type 1 diabetes, we examined the interval between episodes of severe hypoglycemia (SH) as a risk factor for recurrent SH or hypoglycemic coma (HC). Methods: This was a large longitudinal observational study. Using the DPV Diabetes Prospective follow‐up data, we analyzed frequency and timing of recurrent SH (defined as requiring assistance from another person) and HC (loss of consciousness or seizures) in 14 177 youths with type 1 diabetes aged <20 years and at least 5 years of follow‐up. Results: Among 14 177 patients with type 1 diabetes, 72% (90%) had no, 14% (6.8%) had 1 and 14% (3.2%) >1 SH (HC). SH or HC in the last year of observation was highest with SH in the previous year (odds ratio [OR] 4.7 [CI 4.0‐5.5]/4.6 [CI 3.6‐6.0]), but remained elevated even 4 years after an episode (OR 2.0 [CI 1.6‐2.7]/2.2 [CI 1.5‐3.1]). The proportion of patients who experienced SH or HC during the last year of observation was highest with SH/HC recorded during the previous year (23% for SH and 13% for HC) and lowest in those with no event (4.6% for SH and 2% for HC) in the initial 4 years of observation. Conclusions: Even 4 years after an episode of SH/HC, risk for SH/HC remains higher compared to children who never experienced SH/HC. Clinicians should continue to regularly track hypoglycemia history at every visit, adjust diabetes education and therapy in order to avoid recurrences.